Optimization of Rosenbrock function usingGenetic Algorithm - Ankita, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Nowadays, Optimization is the most interesting problems to be studied. It is a process of selecting the best alternative among a given set of options. In the past few decades, a lot of optimization algorithms came into existence to solve NP Hard problems. Genetic Algorithm is one of thepopulations based meta-heuristic to solve such problems. Different benchmark functions are available to test the performance ofoptimization algorithms. Rosenbrock function is a popular test problem for optimization based algorithms. This paper presents experimental results on optimization of Rosenbrock function used for performance evaluation of Genetic Algorithm.